Accounting for the influence of granule size distribution in nanocomposites - A. N. Yurasov; M. M. Yashin (Российский технологический журнал)
This paper discusses the effect of the distribution of the granules size in nanocomposites on physical properties within the framework of the quasi-classical size effect. Methods of effective medium for describing nanocomposites are discussed. This paper also notes and discusses the contribution of various mechanisms that affect the optical and magneto-optical properties of such structures, especially in the IR region of the spectrum, where the quasi-classical dimensional effect is most pronounced. The Droude-Lorentz mode describes the contribution of the dimensional effect to the diagonal and non-diagonal components of the effective medium's permittivity tensor. The lognormal distribution of the granule size characteristic of many nanostructures is considered. Based on this approach, the dependences of the standard deviation on the value of the integral as a function of the average size of the granules were obtained. Based on the normalization condition, the numerical value of the standard deviation of the r values and the average particle size were analytically determined. This paper also discusses the fundamental significance of the results obtained – the possibility of applying this approach to all possible distributions. The found value of the average size of nanocomposite granules makes it possible to model various properties of nanocomposite structures, first of all, optical and magneto-optical properties, with the help of known methods within the framework of the effective medium approximation. This is especially important for describing the percolation transition in nanocomposites. The problem being solved is important and relevant, since many interesting and important effects are realized in such magnetic nanocomposites, such as the magneto-optical Kerr effect, the anomalous Hall effect, the giant magnetoresistance, and many others. The results obtained allow us to better describe materials that are widely used in modern electronics and nanoelectronics.